Ethnicity differentials in academic achievements: The role of time investments - Le, Huong; Nguyen, Ha; Mitrou, Francis; Taylor, Catherine; Connelly, Luke; Zubrick, Stephen (My University, 2020)
In most English-speaking countries, the children of Asian immigrants have better academic outcomes than other children, yet the underlying causes of their advantages are unclear. Using decade-long time use diaries on two cohorts of children, we present new evidence that children of Asian immigrants spend more time than their peers on educational activities beginning at school entry and that the ethnicity gap in the time allocated to educational activities increases as children age. We can attribute the academic advantage of children of Asian immigrants mainly to their allocating more time to educational activities or their favorable initial cognitive abilities, not to socio-demographics or so-called “tiger parenting” styles. Furthermore, our results show substantial heterogeneity in the contributions of initial cognitive abilities and time allocations by test subjects, children’s ages, and points of the test score distribution.
Journal of Population Economics
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Culture and language; Families and relationships; Identity; Intergenerational transfer; International comparison; Labour market; Learning, education and training; Lifestyle; Migration and settlement; Social engagement